Crystallisation of iPB-1 based on preserved helix conformation. (2nd March 2020) - Li, Jingqing; de Claville Christiansen, Jesper; Yu, Donghong; Jiang, Shichun
Abstract: The intriguing problem during polymer crystallisation is to understand the crystal formation and transition, in particular the initiation in a liquid melt close to solid crystals and one solid crystal close to another. Polymorphic isotactic polybutene-1 (iPB-1) usually crystallises into kinetically favoured metastable form II from melt and then spontaneously transits to thermodynamically stable form I. Keeping in mind that polymer crystallisation is controlled by temperature-dependent prior chain conformation formation, we first successfully conserved form-I-favoured 3/1 helix conformation at low temperatures and determined its decomposition temperature as T d, 3/1  = 132 °C. The detailed temperature-dependent helix conformation evolution of iPB-1 during the cooling/heating processes was outlined and the subsequent easy direct form I crystallisation via necessary diffusion and alignment of the preserved 3/1 helix conformation was deduced. The results would be helpful to understand the helix conformation roles in polymer crystallisation, polymorph selection and crystal transition. Graphical abstract: Image 1 Highlights: The 3/1 helix conformation was conserved at T low  = 30 °C below T cr  = 35 °C prior to direct form I crystallisation. Decomposition temperature of the preserved form-I-favoured 3/1 helix conformation was determined as T d, 3/1  = 132 °C. The temperature-dependent helix conformation evolution and entropy of iPB-1 were outlined. The iPB-1 crystallisation in presence of preserved 3/1 helix conformation via diffusion and alignment was proposed.